The Review of Zakat Literacy: Legal Awareness Zakat Concept in Islamic Philanthropy Practies - Nugraha, Ahmad Lukman; Athoillah, Mohamad Anton; Ruhendi, Ateng; Safei, Abdulah (ASFA Foundation, 2025)
This article aims to review the concept of zakat literacy to encourage the maximization of zakat potential. The research method used is qualitative in the form of a literature study. The data obtained are sourced from books, scientific journals, and reports on zakat. The results of this study show that PUSKAZ-BAZNAS mapped two parts that became important points in increasing zakat literacy, namely; Basic knowledge and advanced knowledge. However, the authors have not found any follow-up to the measures of understanding mapped by BAZNAS. Literacy is a projection or series of programs applicable. Zakat literacy not only measures the level of understanding of zakat but also leads to changes in behavior. Awareness of the zakat law will have an impact, especially on behavior change. Awareness of the law of zakat is critical to realize behavior. Four indicators of awareness of zakat law, namely; 1) Knowledge of zakat law, 2) understanding of zakat law, 3) attitude towards zakat law, and 4) legal behavior to perform zakat.